2015
DOI: 10.5541/ijot.5000130524
|View full text |Cite
|
Sign up to set email alerts
|

Conductometric Studies on the Effect of Temperature and Tetramethylammonium Bromide Salt on the Micellization of Cetyltrimethylammonium Bromide in Aqueous Medium

Abstract: The subject of this study concerns the effect of temperature and Cetyltrimethyl ammonium bromide (CTABr) S  ) for the micelle system were estimated by applying the phase separation model while the data obtained allowed access to their usability on the micellization process. Enthalpy -entropy compensation was observed, with a constant compensation temperature of 296K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…Herein, the observed cmc of pure DTAC and DTAC‐CTAB mixed system decreases with the rise of the temperature (Tables ). Again, the cmc of the pure CTAB rises with the augment of the temperature, which is in well agreement with the literature . There was no specific reason for choosing urea except to examine the effect of the urea that is found in the human being.…”
Section: Resultssupporting
confidence: 89%
“…Herein, the observed cmc of pure DTAC and DTAC‐CTAB mixed system decreases with the rise of the temperature (Tables ). Again, the cmc of the pure CTAB rises with the augment of the temperature, which is in well agreement with the literature . There was no specific reason for choosing urea except to examine the effect of the urea that is found in the human being.…”
Section: Resultssupporting
confidence: 89%
“…So, there should be an influence of the glucose on the performance of amphiphiles which are utilized in the formulations of medicines. Our previously reported cmc value for TTAB in H 2 O at 303.15 K is 3.63 mmol kg À1 which agree with literature values (Alam et al, 2019a;Clint, 1975;Sristy et al, 2019); however, at the same condition, the cmc of pure CTAB (0.92 mmol kg À1 ) is also come to an agreement with the literature values (Esan et al, 2015;Hoque et al, 2017Hoque et al, , 2018a. Khosharay et al also obtained a cmc value of 0.823 mmol L À1 for CTAB at 298.15 K using surface tension measurement technique (Khosharay et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…It is reported that with the growing concentration of electrolytes, the size and shape of amphiphile aggregate change from spherical to non-spherical form. The adsorption of surfactants at the air and water interface is affected by the robust electrostatic interaction between the amphiphilic molecules (Clint, 1975;Esan et al, 2015;Hoque et al, 2017Hoque et al, , 2018aMehta et al, 2005). As a result, the degree of adsorption can be expected to be significantly different as compared to the absence of electrolytes in the surfactant solution.…”
Section: Introductionmentioning
confidence: 99%
“…The physical methods for CMC determination includes conductivity, solubility, viscosity, light scattering, measuring the surface tension by Wiebelmy slide method or by the method of maximum bubble pressure, measurement of ion activity and by dye incorporation method, Gel filtration spectrophtometrically and counter ion magnetic resonance [2][3][4][5][6]. Some authors had been used the conductivity measurements to study the micellization of; SDS surfactant in water and in propanol-water mixed solvent [7][8][9][10][11][12], other surfactant [13,14] and ionic liquids [15][16][17][18][19]. The density measurements had been used to calculate the molar volume of some surfactants [20] and other substances in different solutions [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%